Metal–insulator transition in the quasi-one-dimensional transport of fractional quantum hall states. (28th April 2015) - Xiang, S; Fuji, K; Sato, S; Xiao, S; Bird, J P; Aoki, N; Ochiai, Y
Abstract: We investigate edge state transmission in quantum point contacts (QPCs) in the fractional quantum-Hall regime, finding behavior reminiscent of a metal–insulator transition. The transition is suggested by an unusual behavior of the differential conductance in the fractional-quantum-Hall regime, and by the presence of a fixed point and universal scaling in the temperature dependence of the linear conductance. Noting that the 0.7 feature evolves continuously into a last fractional plateau at high magnetic fields, we suggest that this still unresolved feature may itself be viewed as a manifestation of a local, microscopic, metal–insulator transition.